Pengaruh Pemberian Ekstrak Daun Salung (Psychotria viridiflora) terhadap Glukosa Darah Mencit (Mus musculus) - Niki Dwi Dia Dara; Aceng Ruyani; Rendy Wikrama Wardana; Afrizal Mayub; Bhakti Karyadi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to determine the effect of salung (Psychotria viridiflora) leaf extract on blood glucose levels in hyperglycemic mice (Mus musculus). A total of 25 mice weighing 20–40 grams were divided into five treatment groups: P1 (negative control: feed and distilled water), P2 (alloxan 10 mg/kg BW + glibenclamide 0.1 mg/kg BW), P3 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0112 g/kg BW), P4 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0225 g/kg BW), and P5 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0337 g/kg BW). Blood glucose levels were measured four times—on days 0, 6, 12, and 18—covering baseline measurement, post-alloxan induction, and after treatment administration. The results showed that the highest dose (0.0337 g/kg BW) was the most effective in reducing blood glucose levels in alloxan-induced mice, with an effect comparable to the standard drug glibenclamide. In conclusion, P. viridiflora leaf extract has potential as an alternative herbal antidiabetic therapy in M. musculus.  Keywords: Antidiabetic, Blood Glucose, Extract Leaf, Hyperglycemia, Mus musculus, Psychotria viridiflora